PERANCANGAN PEMETAAN MODEL KOMPETENSI DI TEMPAT KERJA BERBASIS SISTEM OLAP - Raswa - Raswa (Jurnal Teknologi Terapan, 2020)
Graduate profile matches with  needed competency by the workplace to be very important learning target sought in the vocational education. This research worshe a  On Line Analyical Processing (OLAP) System Design, it can solve to competency model mapping problem, that is done and developed in workplace. This design aim to be helped in formulation of the outcome’s profile, and to be   used as source’s information to curriculum development and learning outcome on vocational education. This research is designed as engeneering research with laboratory-explanatory on quasi-experiment by incremental model, and data analytical technic is descriptive-evaluative. As research object is The Network Administrator of the Competency Ocupation Mapping on Communication and Imformation Technic.The conclutions obtained the competency model can be extracted to be multidimensional data so by implementation the OLAP system design can be founded the critical aspects of the competency model. Futher research recommendations are needed  field research in OLAP system development for the mapping of competency model by Machine Learning and Deep Learning Technology.